Evaluation of serum lipid profile in cases of pre-eclampsia and eclampsia - Mittal, Meena; Kulkarni, C. V.; Panchonia, Ashok; Mittal, R. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: According to the current knowledge, rise in the serum triglyceride level is a major contributor in the pathogenesis of preeclampsia and eclampsia. The present study was designed to compare the changes in lipid profile in normal pregnancy, pre-eclampsia & eclampsia cases. Methods: A case control study was done consisting of total 100 study subjects, 75 already diagnosed pre-eclamptic & eclamptic women and 25 normotensive pregnant women. Age range was 18-35 years, gestational age 28 weeks to term were included. Serum Total Cholesterol (TC), triglyceride and HDL-cholesterol by enzymatic colorimetric method were done. Results: Results showed that level of serum triglycerides in mild pre-eclampsia (156.22 ± 66.5 mg/dl), severe pre-eclampsia (168.30 ± 68.1 mg/dl) & eclampsia (224.89 ± 84.40 mg/dl) as compared to normal pregnant women (130.95 ± 44.64 mg/dl) was increased significantly (P <0.05). Other parameters TC, HDL-C, LDL-C were not changed significantly. Conclusions: The findings of the present study are consistent with previous studies, suggesting increased levels of serum triglyceride as an important factor in the pathological process of preeclampsia & eclampsia. This may help in developing strategies for prevention or early diagnosis of the disorder.